2009
DOI: 10.1111/j.1463-1318.2009.01933.x
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of anal fistula plug in fistula‐in‐ano: a systematic review

Abstract: Anal fistula plug procedure has a success rate ranging from 24% to 92% in different studies. In prospective studies of complex fistula-in-ano, there was a moderate success rate of 35-87%. As AFP is associated with low morbidity and sepsis, it appears to be a safe procedure. Further randomized controlled trials studying objective parameters of fistula healing are needed to substantiate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
1
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(73 citation statements)
references
References 30 publications
(45 reference statements)
0
66
1
6
Order By: Relevance
“…Since then, several studies on the AFP have been reported with variable results. A systematic review, based on observational studies, reported that the AFP has a moderate success rate of 35%-87% for complex fistula-in-ano [14] . In the present report, we performed a meta-analysis comparing the AFP and the MAF with the objective of evaluating the efficacy of the AFP for the treatment of patients with a complex fistula-in-ano.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, several studies on the AFP have been reported with variable results. A systematic review, based on observational studies, reported that the AFP has a moderate success rate of 35%-87% for complex fistula-in-ano [14] . In the present report, we performed a meta-analysis comparing the AFP and the MAF with the objective of evaluating the efficacy of the AFP for the treatment of patients with a complex fistula-in-ano.…”
Section: Introductionmentioning
confidence: 99%
“…However, the literature mentions a high rate of recurrences and infective complications (sepsis, suppuration, or abscesses) following the use of such devices in anorectal conditions [3,4]. It is not unreasonable to expect some of these complications or recurrences when the plug is being used in a recto-urethral repair as well.…”
Section: Editormentioning
confidence: 99%
“…Insgesamt wurden die Plug-Technik und weitere neue Verfahren in diversen Reviews aufgearbeitet [82,139,214,234,292,296,332,402]. Cirocchi et al [82] …”
Section: Reviews Zur Plug-technikunclassified